Penerapan System Evaluasi Pembelajaran Checking-Up Sebagai Upaya Mempermudah Sekolah Berbasis Keagamaan Dalam Meningkatkan Kompetensi Siswa Dalam Belajar - Amnah; M, Meiliza; Puvita Salma, Cika; Andhika, Restu; Rofilah Akmal, Dini (Jurnal Pengabdian Masyarakat Tapis Berseri (JPMTB), 2025)
Madrasah Aliyah Bandar Surabaya which has a location quite far from Bandar Lampung with an area of 2,500m2, is a school at the same level as Senior High School (SMA) which is located on Rajawali Surabaya Ilir street, Seputih Surabaya district. The principal of MA Aliyah Bandar Surabaya is Mr. Dedi Hidayat, S.Pd. Madrasah Aliyah Bandar Surabaya was established in 2007 and has 28 classes with a total of + 500 students. This service will involve teachers and students of Madrasah Aliyah Bandar Surabaya who are sitting in grade XII who are ready to be deployed to the community, must have the skills needed by the world of work, especially basic IT skills. Madrasah Aliyah Bandar Surabaya has never received similar training for Madrasah Aliyah Bandar Surabaya students from higher education, so the service team took the initiative to carry out the program for grade XII students, with the aim of increasing skills in facing the world of work. With the training needed by Madrasah Aliyah Bandar Surabaya students in grade XII, it is hoped that Madrasah Aliyah Bandar Surabaya students will be more confident and quickly absorbed in the world of work, so as to make a good contribution to the community and have a positive effect on Madrasah Aliyah Bandar Surabaya, which has succeeded in equipping its students with skills that are relevant to the current world of work. The application of the Learning Evaluation system uses the Checking-Up method Where teachers can provide questions that can measure students' absorption in subjects, in this service TIM focuses on the use of Technology and Leadership subject applications.